Detection of Intrusions and Malware, and Vulnerability Assessment : 9th International Conference, DIMVA 2012, Heraklion, Crete, Greece, July 26-27, 2012, Revised Selected Papers - Markatos, Evangelos; Robertson, William; Flegel, Ulrich (Lecture notes in computer science, 2013)
This book constitutes the refereed post-proceedings of the 9th International Conference on Detection of Intrusions and Malware, and Vulnerability Assessment, DIMVA 2012, held in Heraklion, Crete, Greece, in July 2012. The 10 revised full papers presented together with 4 short papers were carefully reviewed and selected from 44 submissions. The papers are organized in topical sections on malware, mobile security, secure design, and intrusion detection systems (IDS).